2016
DOI: 10.1111/trf.13594
|View full text |Cite
|
Sign up to set email alerts
|

Platelet transfusion therapy in sub‐Saharan Africa: bacterial contamination, recipient characteristics, and acute transfusion reactions

Abstract: Background Little data are available on bacterial contamination (BC) of platelet units or acute transfusion reactions to platelet transfusions (PT) in sub-Saharan Africa (SSA). Methods This prospective observational study evaluated the rate of BC of whole blood derived platelet units (WB-PU), the utility of performing Gram stains (GS) to prevent septic reactions, characteristics of patients receiving PT and the rate of acute reactions associated with PT at the Uganda Cancer Institute in Kampala, Uganda. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 31 publications
(62 reference statements)
0
27
1
Order By: Relevance
“…Compared to what has been reported from other African countries ,the average unconfirmed South African AP contamination rate of 2·7% is comparable to the prevalence data from Uganda, below the rates published in Ghana and Zimbabwe and 10‐fold higher than the rate quoted for the high‐income countries .…”
Section: Discussioncontrasting
confidence: 49%
“…Compared to what has been reported from other African countries ,the average unconfirmed South African AP contamination rate of 2·7% is comparable to the prevalence data from Uganda, below the rates published in Ghana and Zimbabwe and 10‐fold higher than the rate quoted for the high‐income countries .…”
Section: Discussioncontrasting
confidence: 49%
“…Testing itself also has limitations. As one example, Gram staining alone, which is used by many hospitals, has been shown to be an insensitive screening measure of bacterial contamination …”
Section: Discussionmentioning
confidence: 99%
“…Safeguards against bacterial contamination such as diversion pouches and blood culture, which are in routine use in high‐income countries (HICs), are not widely available and/or applied in resource‐constrained settings. Studies in Africa have shown bacterial contamination rates range from 2% to 17·5%, compared to an estimated 1 of 3000 units in the United States .…”
Section: Discussionmentioning
confidence: 99%